The role of registerial expertise in translators’ logical choices: A case study of the Chinese medicine classic Huang Di Nei Jing - Yue, Yan (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
Expertise as an indicator of a translator’s competence has experienced a growing amount of research interest recently, but little attention has been paid to the role of registerial expertise, especially in medical translation. This study aims to carry out a systemic functional investigation of the role that a translator’s registerial expertise plays, namely medical expertise, in the translations of Huang Di Nei Jing, the most ancient and important medical classic in traditional Chinese medicine (TCM). The focus is on the logical choices made by both clinician and non-clinician translators. The findings report a few interesting patterns in the translators’ logical choices in relation to their medical expertise. Firstly, clinician translators tend to have a higher degree of intervention through their strategic logical choices, and their translations tend to be more grammatically intricate. They are also found to have a stronger sense of the logical relationships in modelling medical events according to their importance. Further, although mother tongue is found to be impactful on the translators’ logical choices to some degree, it is the registerial expertise that has been found to play the major role. The evidence reported in this study suggests that the translator’s registerial expertise should be included as an important component of translator training.